Cultural Heritage Management of Local Product "Ale": A Strategy for Digital Era Documenting and Preservation of Local Wisdom - Patintingan, Mersilina L.; Pakiding, Yulius; Pare, Ernita (Jurnal Ilmiah Global Education, 2024)
The cultural history of the indigenous product 'Ale' a mat constructed from a plant analogous to rice, constitutes a significant aspect of the ancestral wisdom transmitted through generations within Toraja civilization. Nonetheless, throughout time, its preservation and maintenance encounter numerous obstacles, particularly in sustaining its viability in the digital age. This project seeks to discover solutions for managing the cultural legacy of 'Ale' products through proper documentation and the preservation of local wisdom. This research employs a qualitative methodology, utilizing data collection approaches such as interviews, observations, and documentary analysis. The research findings indicate that digital technologies, including social media platforms and web-based applications, can effectively document and present 'Ale' items to a global audience. Moreover, collaboration among local communities, scholars, and the government is essential for preserving the sustainability of 'Ale' products and the indigenous knowledge they embody. This research advances the formulation of technology-driven solutions for the protection of cultural assets in the future.